Development of a 1kW SOFC power package for residential application - Nam, S.W.; Hong, S.-A.; Seo, S.-H.; Yoo, Y.-S. (EFC 2009 - Piero Lunghi Conference, Proceedings of the 3rd European Fuel Cell Technology and Applications Conference, 2009)
A compact 1kW power package was fabricated by integrating a SOFC stack and sub systems including a fuel reforming system and a heat recovery system. The package was operated using natural gas as a fuel. It was found that electrical efficiency over 30% (HHV) at high current densities.